Beginning PHP and MySQL E-Commerce 2nd Edition - Darie, Cristian (Apress, 2012)
Welcome to the second edition of Beginning PHP and MySQL E-Commerce: From Novice to Professional! This book is a practical, step-by-step PHP and MySQL tutorial that teaches you real-world development practices. Guiding you through every step of the design and build process, this tutorial will teach you how to create high-quality, fully featured, extendable e-commerce web sites. Over the course of this book, you will develop the necessary skills to get your business up on the Web and available to a worldwide audience. In each chapter, you will implement and test new features of your e-commerce web site, and you will learn the theoretical foundations required to understand the implementation details. The features are presented in increasing complexity as you advance throughout this book, so that your journey will be as pleasant and painless as possible. By the end, you’ll understand the concepts, and you’ll have the knowledge to create your own powerful web sites. Owners of the first edition will find that a large part of the book has been rewritten and many features have been added, as a result of the advances in the web development scene and the extensive feedback we’ve received from the readers of the first edition. Now, you’ll find the book teaches you AJAX techniques, how to implement search engine optimization and product attributes, and many other exciting features.